Hubungan Kepemimpinan Situasional dengan Efektivitas Tim Medis di Rumah Sakit Prima Husada Sengkang - Anugerah Yanuar Azis; Ruslang Ruslang; Muhammad Amaliah S (Lentera Pena Cendekia, 2025)
Hospitals are complex organizations in which leadership serves as a determining factor for the quality of services provided to patients. Situational leadership emphasizes the flexibility of leaders in adapting their style according to the conditions and maturity level of team members to achieve optimal organizational effectiveness. This study aimed to comprehensively analyze the relationship between situational leadership and the effectiveness of medical teams at Prima Husada Sengkang Hospital. A quantitative cross-sectional design was employed in this study, which was conducted in September 2025. The study sample consisted of 32 medical team members selected using purposive sampling. Data were collected using Likert-scale questionnaires to measure situational leadership (12 items) and team effectiveness (10 items). Data analysis was performed using Pearson’s correlation test. Univariate analysis showed that the average score of situational leadership was 43.6 and team effectiveness was 37.8, both categorized as moderate to high. Bivariate analysis revealed a significant positive relationship between situational leadership and medical team effectiveness, with a correlation coefficient of r = 0.612 and a p-value of 0.000.These findings indicate that higher levels of situational leadership are associated with greater effectiveness of medical teams in achieving goals, coordination, and job satisfaction. The adaptive ability of leaders to assess team situations and provide appropriate guidance is crucial in the dynamic hospital environment. It can be concluded that there is a significant relationship between situational leadership and medical team effectiveness at Prima Husada Sengkang Hospital, which warrants management attention to enhance institutional performance.